After Forever – The Continuity Model of Family Business Goal Setting: A Theoretical Framework and Practical Applications - Heidrich, Balázs; Vajdovich, Nóra (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
This study introduces a continuity model grounded in goal-setting theory to examine the formulation and influence of goals on the continuity of family businesses. Rooted in Tagiuri and Davis's (1996) three-circle framework, the model integrates the dimensions of family, business, and ownership, highlighting their individual and collective impact on goal-setting processes. Empirical findings emphasize the importance of explicit and latent goals within the family dimension, organizational objectives shaped by resource availability, and the critical role of leadership in aligning these goals. The research highlights the leader's personality values and entrepreneurial orientation—including risk-taking, innovation, and strategic vision—as central determinants in the establishment and execution of business strategies. Findings from the wine industry illustrate how leaders effectively reconcile personal, familial, and organizational goals while adapting to internal and external moderating factors, such as generational transitions and dynamic market environments. The model bridges theoretical insights and practical applications, offering a robust framework for academics and practitioners to enhance the continuity and sustainable growth of family enterprises.